1995
DOI: 10.1038/375791a0
|View full text |Cite
|
Sign up to set email alerts
|

Absence of radius and ulna in mice lacking hoxa-11 andhoxd-11

Abstract: Mice with targeted disruptions in Hox genes have been generated to evaluate the role of the Hox complex in determining the mammalian body plan. This complex of 38 genes encodes transcription factors that specify regional information along the embryonic axes. Early in vertebrate evolution an ancestral complex shared with invertebrates was duplicated twice to give rise to the four linkage groups (Hox A, B, C and D). As a consequence, corresponding genes on the separate linkage groups, called paralogues, are most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
426
1
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 569 publications
(443 citation statements)
references
References 28 publications
13
426
1
3
Order By: Relevance
“…Recent loss-of-function studies in mice demonstrated a pivotal role for Hox10 and Hox11 in metanephric kidney development (Gong et al, 2007;Yallowitz et al, 2009Yallowitz et al, , 2011. Loss of paralogous group 11 genes causes mesenchymal defects exhibited in aberrant branching morphogenesis or agenesis (Davis et al, 1995;Patterson et al, 2001;Wellik et al, 2002) and results in altered expression of many kidneys markers, including Gdnf, Six-2, Bf-2, Pax-2, and Integrin a8 (Patterson et al, 2001;Valerius et al, 2002;Wellik et al, 2002;Mugford et al, 2008). Loss of paralogous Hox10 genes causes the loss of cortical stromal cell function results in undifferentiated kidney capsule along with aberrant ureter branching (Yallowitz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent loss-of-function studies in mice demonstrated a pivotal role for Hox10 and Hox11 in metanephric kidney development (Gong et al, 2007;Yallowitz et al, 2009Yallowitz et al, , 2011. Loss of paralogous group 11 genes causes mesenchymal defects exhibited in aberrant branching morphogenesis or agenesis (Davis et al, 1995;Patterson et al, 2001;Wellik et al, 2002) and results in altered expression of many kidneys markers, including Gdnf, Six-2, Bf-2, Pax-2, and Integrin a8 (Patterson et al, 2001;Valerius et al, 2002;Wellik et al, 2002;Mugford et al, 2008). Loss of paralogous Hox10 genes causes the loss of cortical stromal cell function results in undifferentiated kidney capsule along with aberrant ureter branching (Yallowitz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this idea, it has been demonstrated that Hox paralogues function together to specify both the axial and appendicular skeleton of the mouse (Condie and Capecchi, 1994;Davis et al, 1995;Horan et al, 1995). Additionally, it has been shown (hoxd-11/hoxd-12) and (hoxd-12/hoxd-13) transheterozygotes.…”
Section: Figmentioning
confidence: 68%
“…These genes are activated in a strictly regulated temporal and spatial pattern during development such that the more 3′ gene (hoxd-12) is expressed earlier and in a more proximal domain than the more 5′ gene (hoxd-13; Duboule, 1992;Izpisúa-Belmonte and Duboule, 1992). This feature of temporal and spatial colinearity of Hox genes may play an important role in limb patterning by determining regional identity along the appendicular axis and controlling the properly timed cellular proliferations required for the building of the limb (Davis et al, 1995;Duboule, 1995). To analyze the role of these genes in limb development, we have created targeted disruptions in mice (Capecchi, 1989).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, elements of the skeleton develop abnormally when Hox genes are misexpressed in transgenic mice (Charite et al, 1994;Jegalian and DeRobertis, 1992;Kessel et al, 1990;Lufkin et al, 1992;Pollock et al, 1992). Similarly, the disruption of Hox genes by targeted mutagenesis leads to alterations in the skeleton (Boulet and Capecchi, 1996;Boulet and Capecchi, 2002;Capecchi, 1993, 1994;Capecchi, 1994, 1996;Davis et al, 1995;Favier et al, 1995;Favier et al, 1996;Fromental-Ramain et al, 1996a;Fromental-Ramain et al, 1996b;Horan et al, 1995a;Horan et al, 1994;Kostic and Capecchi, 1994;LeMouellic et al, 1989;RamirezSolis et al, 1993;Rancourt et al, 1995;Rijli et al, 1994;Rijli et al, 1993;Rijli et al, 1995;Saegusa et al, 1996;Small and Potter, 1995;Suemori et al, 1995. Analogous to mutant phenotypes in the fruitfly Drosophila, the pattern abnormalities in vertebral shape and identity have generally been interpreted as homeotic transformations.…”
Section: Regionalization Along the Anterior-posterior Axis: Hox Genesmentioning
confidence: 99%